2010
DOI: 10.1007/s00702-010-0445-0
|View full text |Cite
|
Sign up to set email alerts
|

Chronic variable stress induces oxidative stress and decreases butyrylcholinesterase activity in blood of rats

Abstract: Depressive disorders, including major depression, are serious and disabling, whose mechanisms are not clearly understood. Since life stressors contribute in some fashion to depression, chronic variable stress (CVS) has been used as an animal model of depression. In the present study we evaluated some parameters of oxidative stress [thiobarbituric acid reactive substances (TBARS), catalase (CAT), superoxide dismutase (SOD) and glutathione peroxidase (GPx)], and inflammatory markers (interleukin 6, C reactive pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 80 publications
0
16
1
Order By: Relevance
“…CVS chronic variable stress The CVS procedure was developed as an animal model of depression that presents three important characteristics: the inducing conditions are relatively realistic, the focus of the model is a core symptom of depression, anhedonia, and the protracted time course of the model is suitable for investigating the effects of chronic drug treatments [31]. A series of publications have reported that the CVS procedure causes decreased intake of sucrose solutions (or pellets) [32][33][34][35], impairments in other measures of hedonic reactivity such as place preference conditioning [36,37] and brain stimulation reward [38,39], decreased sexual and aggressive behaviors [40,41] and self-care [42][43][44], in addition to changes in sleep architecture [39,45]. Moreover, these behavioral changes are reversed by chronic treatment with all classes of clinically-effective antidepressant drugs, but not by drugs known to be ineffective as antidepressants.…”
Section: Discussionmentioning
confidence: 99%
“…CVS chronic variable stress The CVS procedure was developed as an animal model of depression that presents three important characteristics: the inducing conditions are relatively realistic, the focus of the model is a core symptom of depression, anhedonia, and the protracted time course of the model is suitable for investigating the effects of chronic drug treatments [31]. A series of publications have reported that the CVS procedure causes decreased intake of sucrose solutions (or pellets) [32][33][34][35], impairments in other measures of hedonic reactivity such as place preference conditioning [36,37] and brain stimulation reward [38,39], decreased sexual and aggressive behaviors [40,41] and self-care [42][43][44], in addition to changes in sleep architecture [39,45]. Moreover, these behavioral changes are reversed by chronic treatment with all classes of clinically-effective antidepressant drugs, but not by drugs known to be ineffective as antidepressants.…”
Section: Discussionmentioning
confidence: 99%
“…Its activity altered in numbers of diseases [29,30,37]. SOD activity found to be decreased in different depressive animal model [38,39]. Rybka et al, reported low levels of SOD in the cases of major depression as compared to healthy controls but this was not significant [22].…”
Section: Discussionmentioning
confidence: 99%
“…Malondialdehyde (MDA) is a product of lipid peroxidation caused by reactive oxygen species and is therefore an indicator of lipid oxidation injury [9]. Tagliari and Lucca observed an obvious decrease in SOD and CAT activities with increasing MDA levels in chronic unpredicted mild stress-induced or variable stress-induced depressive rats [7,10]. Therefore, another aim of antidepression treatment would be to increase the activity of SOD and CAT and decrease the levels of MDA.…”
Section: Introductionmentioning
confidence: 97%
“…Oxidative stress in the brain may also be involved in the development of depression [7]. Free radicals, which play a role in mitosis, are mainly scavenged by elements of the antioxidative stress system, including superoxide dismutase (SOD) and catalase (CAT).…”
Section: Introductionmentioning
confidence: 99%